All-optical diode for terahertz optical power rectification based on two-dimensional photonic crystals. (June 2023) - Parandin, Fariborz; Moayed, Mitra; Heidari, Farsad
Abstract: Photonic crystals are one of the most important structures used in the creation of optical devices. Photonic crystals are capable of being used to make optical diodes. The quantity of optical power transferred in the "on" state, from anode to cathode, is one of the most significant criteria in the design of an optical diode, while low optical power is the reverse. Another essential characteristic of an all-optical diode is its simple structure and compact size, which make it easy to manufacture and allow it to be incorporated into optical circuits. In this study, an all-optical diode is designed using the creation of a photonic crystal with a hexagonal lattice and tiny dimensions. To simplify the complexity of the structure, the crystal structure was created using simple line defects and a modest number of point defects. In addition to its rapid transfer of optical power, the suggested diode features a high optical power output while conducting and a negligible output when "off."